A new genus of Phengodidae (Coleoptera) from the Neotropical Region - Vega-Badillo, Viridiana; Zaragoza-Caballero, Santiago; Ivie, Michael A. (Papéis Avulsos de Zoologia, 2020)
Cleicosta, a new genus of Phengodidae containing two new species, C. equatoreana sp. nov., and C. monaguense sp. nov., are described. Additionally, a new combination for Cenophengus breviplumatus Wittmer, 1976 is included. Cleicosta gen. nov., is the thirty-eighth genus assigned to the beetle family Phengodidae in the new world and is also the most morphologically similar to Cenophengus LeConte, 1881. Both genera exhibit clearly separated tentorial pits, vertical frons and simple tarsomeres. In Cleicosta gen. nov., however, the antennal rami are 1.5 times longer than the corresponding antennomere, the pronotum is subquadrate and the elytra are short, reaching the first or second abdominal segment. In addition, it presents an aedeagus with lateral lobes slender, parallel exteriorly, narrowed medially to toothless apex.